A practicum training in inland fisheries course conducted at freshwater aquaculture center CLSU, Muños, Nueva Ecija. - Lantican, Crispin A. (College of Fisheries, University of the Philippines, 1980)
Every graduating fishery students, fisheries 197 is a requirement. It is not simply a requirement but also an exposure of the students to actual training in fish cultivation. It was designed to let the students experience the actual application of aquaculture method and management. The course aims to provide practical experience in various aspects of aquaculture industry which students are made to undergo training where they can apply theoretical knowledge gained in the classroom. This report entitled "practicum training in inland Fisheries course conducted at freshwater aquaculture center" was the evidence of my practical experience. It claims to define, illustrate and elucidate different aspects of the practicum activities conducted at FAC-CLSU, Munoz Nueva Ecija. The training was undertaken during the semestral break (15 October to 10 November, 1979). The daily activities started from 8:00 in the morning until 5:00 in the afternoon, Monday to Friday and 8:00 to 12:00 during Saturdays. Furthermore, we also conducted a series of interviews with the workers of the center. We also made frequent observations on the ponds in order to obtain an additional knowledge how an ideal productive fishpond looks like. Essentially, this course therefore correlates in realistic terms the principle learned in the class and its practical applications.